UPAYA PENINGKATAN HASIL BELAJAR IPS MELALUI MODEL KOOPERATIF TIPE GROUP INVESTIGATION - Badriah (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2020)
The research was conducted on 34 students of class IX MTs Binahasanah Cigugur District Pangandaran Regency consisting of 14 boys and 17 girls. This research was started in August to November 2019. The facts found in social studies learning in class IX MTs Binahasanah Cigugur Pangandaran Regency show that student motivation is low, students still depend on teachers, and learning is still conventional. This is because 15 of the 31 students do not get the minimum passing criteria. Based on this, the researcher conducted cooperative learning with group investigation type to increase the learning motivation of students in order to achieve social studies learning in accordance with the minimum completeness criteria set by the school. After the classroom action research was carried out, at the end of the second cycle the researcher got the target, because the teacher and students who applied the cooperative learning investigative group type got good grades. Researchers take action using the type of investigation group. The learning outcomes of students in cycle II experienced a significant increase, but in cycle I students were still dependent and afraid to express their ideas, but at the end of cycle II learning outcomes increased.